"Exfoliation, Cheese Courses, Emotional Honesty, and Paxil": Masculinity, Neoliberalism, and Postfeminism in the US Hangout Sitcom. (1st September 2021) - Wolfman, Greg
Abstract: This article applies a conjunctural analysis to four US "hangout sitcoms"— Friends, How I Met Your Mother, The Big Bang Theory, and New Girl —to examine the tensions faced by masculinities in a neoliberal era. After establishing the "hangout sitcom" subgenre, I use critical discourse analysis to unpack three male subject positions. The postfeminist male singleton reacts neurotically to a perceived loss of power with a desperate search for true love. The douchebag responds with excessive performances of both masculinity and neoliberal subjectivity, while the househusband' s stable job and long-term heterosexual relationship reflect neoliberalism's relationships with intimacy and the family. I argue that the hangout sitcom, and specifically its representation of masculinities, offers an under-explored opportunity to examine the politics of masculinities, postfeminism, and neoliberalism.